Increased aggressive and affiliative display behavior in intrauterine growth restricted baboons. Issue 3 (16th April 2015) - Huber, Hillary F.; Ford, Susan M.; Bartlett, Thad Q.; Nathanielsz, Peter W.
Abstract Background We hypothesized intrauterine growth restricted offspring (IUGR) demonstrate higher rates of aggression and higher dominance ranks than control (CTR) offspring with normal weight at term; if aggressive behavior is advantageous during resource scarcity, developmental programming may lead to an association between aggression and IUGR. Methods We studied 22 group‐housed baboons (ages 3–5 years). CTR (male n = 8, female n = 5) mothers ate ad libitum. IUGR (male n = 4, female n = 5) mothers were fed 70% feed eaten by CTR mothers during pregnancy and lactation. Results IUGR showed higher rates of aggressive displays (P < 0.01) and friendly displays (P < 0.02). Dominance ranks and physical aggression rates did not differ between groups. Conclusions High rates of IUGR aggressive display might reflect developmental programming of behavioral phenotypes enhancing fitness. Friendly displays may reflect reconciliation. Potential mechanisms include neurodevelopment and learning. Exploration of IUGR as a risk factor for behavioral patterns is important for developing diagnostic and therapeutic strategies.